Resistensi Kaum Homoseksual di Inti Muda Jawa Timur Terhadap Stigma Media Massa - Anggalimea, Angwen (Paradigma, 2022)
his study aims to identify how the resistance of homosexuals in Inti Muda, East Java, to the negative stigma of the mass media. This research is descriptive qualitative, using data collection techniques through observation, interviews, and documentation. Researchers also use a phenomenological approach by Edmund Husserl. Subjects were selected through the snowball sampling technique, researchers obtained samples through a rolling process from one informant to another. The subject of this research is a young core member of East Java who has a sexual orientation as gay. The results of the study show that gay people in Inti Muda Jawa Timur have open resistance. Open resistance is the rejection of an act of discrimination carried out in a systematic, organized, ideological and revolutionary way. For those who dare to speak the truth and are anti-violent, they can at least change people’s mindsets. This is evidenced by the gay people in Inti Muda Jawa Timur, who are organized and actively participate in educational activities, participate in demonstrations while fighting for the RUU TPKS, voice directly or from social media regarding gender issues, and participate in humanitarian activities. Keywords: Homosexuality, Resistance, and Social Solidarity